Teacher's Duties in the Al-Quran Perspective, Tafsir Surah Al-Baqarah Verse 151 - Nurchamidah; Nur Laela; Baso Syafaruddin; Muhammad Hamsah (al-Afkar, Journal For Islamic Studies, 2024)
Some of the teacher's tasks that every teacher should pay attention to and carry out are: 1. Reading Allah's Verses in the first lesson of all lessons in a day. This requires teachers or educational units to make learning the Koran an opening for all learning activities. This is done in order to open the door to Allah SWT's mercy. and prepare students' souls to receive the next lessons. 2. Purify students, where purification includes cleansing from damaged aqidah, from despicable morals, changing and perfecting their reasoning power through divine knowledge towards decisions that are based on sound reason and mature thinking, legal order and civilisation. 3. Teaching the Bible and wisdom, so a teacher must know the needs of students "The first need for Muslims to learn to write is based on the obligation to write the Koran. This can be described at the time when the Prophet chose several people to be his secretaries, who were tasked with writing revelations and writing letters which he sent to kings and leaders to convert to Islam. A teacher indeed forms students so that in the future they will become dignified human beings who are able to change the people around them towards more progress. Such as giving birth to scholars, writers, wisdom experts, leaders, experts in knowledge and insight. 4. Teaches something new, Islam believes that every child born has potential that has been brought to the world since they first entered the world. Therefore, teachers are assigned to have integrated creative thoughts that are able to interpret old things in new language. As far as substance is concerned and making new things useful tools in the future.